2020
DOI: 10.1183/13993003.01857-2019
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy affects adult onset of asthma in offspring: a follow up from birth to age 46 years

Abstract: RationaleEnvironmental tobacco smoke (ETS) exposure increases asthma risk in children. There is limited knowledge of prenatal ETS for adult-onset asthma.ObjectivesTo determine the association between prenatal ETS and adult onset asthma.Measurements and main resultsThe questionnaire and clinical data of 5200 people, free of physician-diagnosed asthma by 31 years of age, who were included in the Northern Finland Birth Cohort 1966 Study was used. The association of maternal smoking during the last 3 months of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Maternal smoking during pregnancy appears to increase the risk for wheeze and asthma even among children who were not exposed to maternal smoking after birth. 19 Our results showing an increased risk for asthma in infants whose mothers smoked during pregnancy agreed with earlier findings of other studies. 2,7,8,14,19 In a birth cohort of 4089 newborn infants followed for 2 years, when the mother had smoked during pregnancy and stopped after that, an increased risk for recurrent wheezing for up to 2 years of age was recorded (adjusted OR, 2.2; 95% CI, 1.3-3.6); maternal otitis media (yes/no) and number of events, diagnosis of bronchiolitis (yes/no), date of the first diagnosis of bronchiolitis and number of episodes, diagnosis of pneumonia/ bronchopneumonia (yes/no), date of the first diagnosis of pneumonia and number of incidences, diagnosis of a life-threatening episode (yes/no), and weight and length at 6 and 12 months of life.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Maternal smoking during pregnancy appears to increase the risk for wheeze and asthma even among children who were not exposed to maternal smoking after birth. 19 Our results showing an increased risk for asthma in infants whose mothers smoked during pregnancy agreed with earlier findings of other studies. 2,7,8,14,19 In a birth cohort of 4089 newborn infants followed for 2 years, when the mother had smoked during pregnancy and stopped after that, an increased risk for recurrent wheezing for up to 2 years of age was recorded (adjusted OR, 2.2; 95% CI, 1.3-3.6); maternal otitis media (yes/no) and number of events, diagnosis of bronchiolitis (yes/no), date of the first diagnosis of bronchiolitis and number of episodes, diagnosis of pneumonia/ bronchopneumonia (yes/no), date of the first diagnosis of pneumonia and number of incidences, diagnosis of a life-threatening episode (yes/no), and weight and length at 6 and 12 months of life.…”
Section: Discussionsupporting
confidence: 93%
“…18 In addition, a pooled analysis of eight European birth cohorts with data of more than 21,000 children showed that maternal smoking during pregnancy was associated with wheeze and asthma in preschool children. 19 In younger children, a meta-analysis of 14 studies showed an increased risk for asthma in children aged ≤2 years (odds ratio [OR], 1.85; 95% confidence interval [CI], 1.35-2.53) in association with prenatal tobacco exposure. 20 However, only a few studies have recorded the impact of maternal smoking during pregnancy on the development of asthma in offspring during the first year of life.…”
Section: Introductionmentioning
confidence: 99%
“…Fifteen covariates were a priori selected based for their potential impact on severe asthma from the data reported in literature: (15,16,31) Lifestyle factors (1 factor) : smoking (never vs. ever) (21,22,32) Early-life factors (6 factors): growing in countryside/farm (33), parental smoking (34), parental asthma and/or allergy (35), severe childhood infections (pneumonia before or during school age or hospitalization due to infection at ≤3 years of age) (36), number of siblings (<2 vs. ≥ 2) (24), birth order (1st vs. other) (24,37,38) Asthma characteristics (1 factor): non-steroidal anti-in ammatory drug (NSAID) -exacerbated respiratory disease (NERD) (17) Chronic comorbidities (3 factors): ≥1 other allergic disease ever [e.g. allergic rhinitis (AR)/allergic conjunctivitis (AC)/atopic dermatitis (AD)] (16,24), nasal polyps (NP) (18), ≥1 other chronic disease(s) (7,21,32).…”
Section: Covariatesmentioning
confidence: 99%
“…RUNX1 is associated with aberrant B cell maturation and is related to acute myeloid or chronic leukemia [118 ]. Our study group showed that association between maternal smoking exposure and incident asthma in adult offspring was accentuated in offspring who had haplotype rs11702779‐AA of RUNX1 gene [119 ].…”
Section: Literature Reviewmentioning
confidence: 99%